Kajian Penyebab Kemiskinan Masyarakat Nelayan di Kampung Tambak Lorok (Fishermen Poverty Causes in Tambak Lorok Village) - Mussadun Mussadun; Putri Nurpratiwi (The Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Abstract. Poverty is caused by natural, cultural as well as structural factors. In coastal areas, the conditions of poverty can be aggravated by climate change phenomena such as coastal inundation and flooding. The village of Tambak Lorok is home for more than 500 poor fishermen households. Three phenomena are considered general problems in Tambak Lorok, i.e. poverty, social pathology, and environmental degradation. In view of these problems, the following research question was formulated: